Role of air core in particle separation in cyclones. (1st March 2013) - Sripriya, R; Meikap, B C; Suresh, N; Chakraborty, S; Bhattacharjee, D; Chandra, S
<x xml:space="preserve">Abstract</x> Detailed studies were carried out to study the effect of air core formation in cyclones on separation of particles using statistical techniques. The design and operating variables of a 100 mm perspex hydrocyclone, both flat bottom and conical, were varied and their effect on different types of air core was studied. The results were analysed using analysis of variance. The % underflow split was the most important variable affecting the air core formation. Studies were also carried out with density tracers under different air core conditions. The studies showed that the lighter particles separated better in the absence of the air core. Particle separation tests were then carried out after suppressing the air core with a metal rod. The separation of lighter particles with specific gravity close to the separating fluid was improved when the air core was suppressed. Numerical simulation studies showed that a higher tangential velocity and a lower radial velocity is the reason for better separation efficiency in the absence of the air core.